Perancangan Interactive Motion Graphic Tentang Wayang Beber Sebagai Sarana Pengenalan Budaya - Pramaditya Hendi Hartono (MAVIS : Jurnal Desain Komunikasi Visual, 2019)
Wayang Beber is a puppet art that appeared in pre-Islamic times and is still developing in certain areas of Java. One of which is Wayang Beber in an area of Pacitan. Wayang Beber Pacitan is played by five people, four people play the instruments such as rebab, kendang, kenong laras slendro and gong while one person act as puppeteer. Wayang beber show begins with a small ritual using scattered flowers, incense, and a few other offerings which are used as a symbol of invoke the salvation from the Almighty God. The way to play Wayang Beber is by rolling the image of the puppet (wayang) one by one until it finishes, then follows the next roll until the story is complete. By the time of its development, Wayang Beber of Pacitan has experienced obstacles due to the lack of public knowledge about what wayang beber is, making it one of the biggest reason why it rarely performed. In order to introduce these puppets (wayang) to be known to the wider community, an interesting way is needed so public are interested. The first step to introduce this puppet(wayang) is by making a video in the form of interactive motion graphic which includes three principal, such as explanation of wayang beber, figures in wayang beber and wayang beber stories. The purpose of making interactive motion graphics is to introduce Wayang Beber of Pacitan to the younger generation through media that are often seen by young people. The final results of this design produced three motion graphic videos, namely an introduction of Wayang Beber of Pacitan, motion graphic of Wayang Beber of Pacitan figures, and motion graphic of Wayang Beber of Pacitan stories. Three of these videos will be disseminated through a video streaming site on the internet, Youtube, with the keyword ‘Interactive Motion Graphic – WayangBeberPacitan’ or also can be accesed by this link https://youtu.be/niWdK1if09k. With an interactive motion graphic about wayang beber primarily aimed at the younger generation, it is expected to be able to make the youngsters become interested in both local culture and content. Through these motion graphics, besides being able to introduce Wayang Beber of Pacitan to the youngster, it is also possible to create other creative content such as films or games adapted from Wayang Beber of Pacitan.